The effect of environmental performance, environmental costs, and company size on financial performance through corporate social responsibility - Evelyn; Sudrajat; Rialdi Azhar (Lighthouse Publishing, 2022)
low environmental management applied by the company amid the modern economic era now causes easy environmental damage. This condition must be overcome so that the company's image remains well respected and financial performance has an increasing income. Financial performance is influenced by several factors, including environmental performance, environmental costs, company size and disclosure of corporate social responsibility. This study aims to determine the effect of environmental performance, environmental costs and company size on financial performance with corporate social responsibility as the intervening variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2020, with a total of 195 companies. Using the purposive sampling method, 38 companies meet the criteria with 114 data sets. The data were analyzed regressively using SmartPLS through descriptive statistical analysis tests, outer models, inner models and hypothesis testing. The results showed that environmental performance, environmental costs and corporate social responsibility had no effect on financial performance, but firm size had a significant positive effect on financial performance. Environmental performance has a significant positive effect on corporate social responsibility. In contrast, environmental costs and company size have no effect on corporate social responsibility, and corporate social responsibility is not proven and can become an intervening variable (mediation) on environmental performance, environmental costs, and company size on financial performance.